Percepção do cirurgião-dentista sobre formação profissional e dificuldades de inserção no mercado de trabalho - Saliba, Nemre Adas [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Prado, Rosana Leal do [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (FapUNIFESP (SciELO), 2012)
Introduction: The evaluation of the perception of graduates is an essential strategy to support the political project educational in universities. Objective: This study aimed to verify the perception of dentists which are working in the labor market, about the difficulties of professional insertion after the graduation, positives and negatives aspects and suggestions regarding the training received. Methodology: This is a qualitative survey conducted with graduates of the years 2000 to 2010, of dentistry course from a Brazilian Public University. A self-administered questionnaire was sent by mail/email to all graduates in the period. The data were transcribed and subjected to content analysis, divided into pre-analysis, characterized by carefully reading floating, material exploration, guidelines for finding the analysis itself. Result: The categories related to the difficulties in early life were: getting a job/workplace, adequate working conditions and low pay, insecurity and confrontation obtained the academic and lack of administrative experience. The perceived positive aspects for the training were: good infrastructure and reputation of the university, integrating teaching-research, teacher-student relationship. The negative aspects comprised the following categories: administrative preparation, lack of integration between content theoretical/ practical, concepts used in the labor market. The suggestions presented are consistent with the difficulties to the beginning of professional life and the negative aspects. Conclusion: The professionals have faced the saturation of the labor market and different reality from those found in academic life. Despite the positive aspects, graduates suggest changes in the course conducted.

Introdução: A avaliação da percepção de egressos é uma estratégia fundamental para subsidiar o projeto político-pedagógico nas universidades. Objetivo: Conhecer a percepção dos cirurgiões-dentistas em atuação no mercado de trabalho a respeito das principais dificuldades para sua inserção profissional, logo após o término da graduação, os aspectos positivos e negativos, e as sugestões em relação à formação acadêmica obtida. Metodologia:  Trata-se de uma pesquisa qualitativa, do tipo inquérito, realizada com egressos dos anos 2000 a 2010, do curso de Odontologia de uma universidade pública brasileira. Foi enviado um questionário autoaplicável por correio/email a todos os egressos no período. Os dados foram transcritos e submetidos à técnica da análise de conteúdo, dividida em pré-análise, caracterizada por leitura com atenção flutuante, e exploração do material, descobrindo orientações para análise propriamente dita. Resultado: As categorias referentes às dificuldades no início da vida profissional foram: conseguir emprego/local de trabalho; condições adequadas de trabalho e baixa remuneração; insegurança e confrontação à formação acadêmica obtida, e falta de experiência administrativa. Os aspectos positivos percebidos em relação à formação foram: boa infraestrutura e reputação da universidade, integração ensino-pesquisa e relacionamento docente-discente. Os aspectos negativos compuseram as categorias: preparo administrativo, falta de integração entre conteúdo teórico e atividade prática, e noções de mercado de trabalho. As sugestões apresentaram-se coerentes às dificuldades para o início da vida profissional e aos aspectos negativos. Conclusão: Os profissionais têm-se deparado com a saturação do mercado de trabalho e realidades diferentes daquelas vivenciadas na formação acadêmica. Os egressos sugeriram mudanças, apesar de relatarem aspectos positivos no curso realizado.
Perception of dentists about professional training and difficulties of insertion in the labor market
Keywords: Dentistry; Education higher; Human resources; Odontologia; Educação superior; Recursos humanos